Offshore Registration of Aircraft - V. L. Tolstykh (Московский журнал международного права, 2020)
INTRODUCTION. The concept of nationality of an aircraft is borrowed from the law of the sea; it is currently enshrined in the Chicago Convention on International Civil Aviation of 1944. Registration performs several functions: firstly, it allows the identification of an aircraft; secondly, it implies the obligation of the state of registration to control its operation; thirdly, it implies the responsibility of the state of registration in the event of failure to exercise such control.MATERIALS AND METHODS. The research was done on the basis of the Chicago Convention of 1944, Cape Town Convention on International Interests in Mobile Equipment 2001, Protocol on Matters Specific to Aircraft Equipment 2001, acts of Russian legislation and acts of offshore legislation, primarily Air Navigation Order 2013. The research involved historical method, methods of formal logic and comparative legal method. The main objective was to develop proposals aimed at increasing the attractiveness of the Russian registry.RESEARCH RESULTS. The Russian registration system has several shortcomings: lack of a codified act; presence of two authorities with overlapping competencies (the Interstate Aviation Committee and the Federal Air Transport Agency); high customs duties on the import of certain types of aircrafts. To this should be added the shortcomings relating to the organization of the registration process: a high degree of its bureaucratization, lengthiness, shortage of qualified specialists, etc. The registration of an aircraft in offshore, on the contrary, implies a number of advantages: speed and “friendliness”, confidentiality of beneficiary data, absence of VAT and customs duties, quality of airworthiness control.DISCUSSION AND CONCLUSIONS. The problem can be resolved imperatively – by fixing the strict obligation of airlines to register aircraft in the domestic registry under the threat of non-issuance or revocation of the operator’s certificate. If, however, this registry does not meet international standards, this measure will adversely affect the development of the aviation sector and the safety of transport. In this regard, the creation of a transparent, holistic and efficient registration system meets the interests of the state no less than the interests of airlines. With regard to the Russian Federation, achieving this goal involves completing a number of tactical tasks, aimed at simplifying formalities, ensuring recognition of the Russian registration system and stimulating trade turnover.